Sedentary Behaviour and Obesity in a Large Cohort of Children - Mitchell, J. A. (2009)
The purpose of this study was to examine the association between sedentary behaviour and obesity among 12-year-old children, while adjusting for moderate-to-vigorous physical activity (MVPA) and other potential confounding variables. Cross-sectional analyses were carried out with data from 5434 children who participated in the Avon Longitudinal Study of Parents and Children (ALSPAC). Fat mass was derived using dual x-ray emission absorptiometry (DXA), and height and weight measurements were used to calculate body mass index (BMI; kg/m(2)). The children wore an accelerometer for seven days. The cut points for sedentary behaviour and MVPA were ≤199 cpm and ≥3600 cpm, respectively. Logistic regression analyses were performed to estimate odds ratios (OR), adjusting for potential confounders of physical activity that included gender, social factors, early life factors and maturation. The minimally adjusted association between sedentary behaviour and obesity was positive, OR=1.18 (1.08, 1.28). After adjusting for the series of potential confounders of physical activity the positive association remained, OR=1.32 (1.14, 1.53). The crude association between 15 minutes of MVPA per day and obesity was negative, OR=0.54 (0.48, 0.62). When 15 minutes of MVPA per day was additionally controlled for in the models, the positive associations between sedentary behaviour and obesity were negated. Sedentary behaviour was positively associated with obesity in the 12-year-old children, but this association was not independent of MVPA; low levels of MVPA among the sedentary children increased the odds of obesity. These finding support the importance of specifically engaging in MVPA during childhood to reduce the prevalence of obesity.